الجريمة الإلكترونية في وسائل الإعلام: التحديات المجتمعية، من المقاربات النظرية في مجال التواصل إلى البناء الخطابي - Rachid Raji; Zakia El Housni (Darul Yasin Al Sys, 2026)
As cybercrime increasingly shapes contemporary digital life, media coverage plays a central role in constructing public understanding of digital threats and insecurity. This paper examines the media coverage and analytical treatment of cybercrime through key theoretical perspectives in media and communication studies, with particular attention to the discursive and narrative strategies used by media institutions to frame cybercrime. Drawing on technological determinism, agenda-setting theory, media effects theory, and new media theory, the study analyzes how media representations of cybercrime oscillate between dramatization, trivialization, and security-oriented framing. The analysis shows that cybercrime is not presented merely as a technical or criminal issue, but as a socially constructed and mediated phenomenon that shapes public perception, influences policy formation, and affects institutional legitimacy. The paper further argues that media institutions play a decisive role in producing collective imaginaries of digital insecurity and in structuring social responses to cyber threats. It concludes that media coverage of cybercrime extends beyond information transmission to become a symbolic process that organizes social representations and influences individual practices. This study contributes to media and communication scholarship by clarifying how theoretical perspectives can explain the role of media in framing cybercrime and its broader social implications.